Comparative Analysis of Soil Microbial Community Structures in Rhizosphere of Two Texture-Differentiated Lotus Root Varieties - Xinni Li; Qiyue Liang; Meiping Gao; Yangxiu Ou; Yifeng Hu; Wen Jiang; Huiping Jiang; Shangdong Yang (Microorganisms, 2025)
To investigate the relationship between the rhizosphere microbial community structure and lotus root texture, the biological properties, and the rhizosphere microbial composition of mealy (ML) and crunchy lotus (CL) varieties were all analyzed using traditional and high-throughput sequencing technologies. The results showed that the ML varieties exhibited significantly lower moisture but higher starch contents than those of CL. Meanwhile, the rhizosphere fungal richness of ML was also significantly higher than that of CL. Moreover, the relative abundances of bacterial phyla and genera, such as Nitrospirota, Bacteroidota, Proteobacteria, and Bacillus, alongside fungal phyla and genera, i.e., Ascomycota and Emericellopsis, were enriched in rhizosphere of ML compared to CL. Functional prediction also revealed that elevated nitrogen cycling, polysaccharide degradation and cellulose breakdown functions could be detected in ML, potentially driving starch accumulation and cell wall modification. These results suggest that rhizosphere microbial composition, particularly nitrogen-cycling bacteria and lignocellulose-degrading fungi, may contribute to texture formation between texture-differentiated lotus root varieties.